TITLE: THE FASCINATING WORLD OF THEME STYLISTICS UNVEILING THE ARTISTIC ASPECTS OF LANGUAGE - Saloxitdinova Shahnoza Jalol qizi; Abdurahmonova Zilola (TADQIQOTLAR.UZ, 2023)
Abstract: This article explores the captivating realm of theme stylistics, an intriguing branch of linguistics that delves into the artistic and aesthetic elements of language. By examining the concept of theme and its significance in discourse analysis, we aim to shed light on the role of theme in enhancing the communicative effectiveness and aesthetic appeal of various forms of written and spoken expression. The article also highlights the relevance of theme stylistics in literary analysis, emphasizing its contribution to the interpretation and appreciation of literary texts. Overall, this article seeks to deepen our understanding of theme stylistics and its implications for language and literature.